A experiência contada por elas mesmas: um estudo acerca da migração sob o olhar e a narrativa da criança - Paula, Karoline Vitorino da Silva de (2018)
This essay has the objective to understand the question of the cultural identity of the Brazilian-Paraguayan people through the speech of children, not only in the locus of their land, but also in their living and social environments. In this way, there is a reflection about the present conjuncture of the Brazilian-Paraguayan people, whose heterogeneous identity draws a specific cultural landscape in the patterns of migration, so that the question of identity is unveiled. Therefore, this essay begins with a reference of a bibliographic research and it‟s followed by a qualitative one, whose sources are the families, and, specifically, the children in their educational and familiar environments. This purpose is justified by the relevance of the discussion surrounding the themes of migration and identity, and also, due to heuristic value that “gives voice” to the informants that are muted in formal debates: the children.